Proteomic Analysis Reveals a Mitochondrial Remodeling of βTC3 Cells in Response to Nanotopography - Maffioli, Elisa; Galli, Alessandra; Nonnis, Simona; Marku, Algerta; Negri, Armando; Piazzoni, Claudio; Milani, Paolo; Lenardi, Cristina; Perego, Carla; Tedeschi, Gabriella (Frontiers in Cell and Developmental Biology, 2020)
Recently, using cluster-assembled zirconia substrates with tailored roughness produced by supersonic cluster beam deposition, we demonstrated that ß-cells can perceive nanoscale features of the substrate and can convert these stimuli into mechanotransductive processes which promote long-term in vitro human islet culture, thus preserving ß-cell differentiation and function. Using the same proteomic approach we now focused on the mitochondrial fraction of βTC3 cells grown on the same Zirconia substrates and characterized the morphological and proteomic modifications induced by the nanostructure. The results suggest that in βTC3 cells mitochondria are perturbed by the nanotopography and activate a program involving metabolism and modulation of their interplay with other organelles. This change induced by the nanostructure can be pro-survival and prime mitochondria for a metabolic switch to match the new cell needs.